The Accuracy of FNAB as Diagnostic Tool For Thyroid Cancer Compared to Anatomical Pathology Results as Gold Standard at Sanjiwani Hospital, Gianyar - Yasa, I Nyoman Wawan Tirtha; Maheswari, Luh Putu Dewanda; Suryawisesa, Ida Bagus Made; Irawan, Hendry; Sudarsa, I Wayan; Bharata, Made Dwi Yoga; Widarsa, I Ketut Tangking (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): JBN (Jurnal Bedah Nasional), 2024)
Aim: The aim of this study was to assess the accuracy of fine needle aspiration biopsy (FNAB) as a diagnostic tool for thyroid cancer in Sanjiwani Hospital, Gianyar. Methods: This study used a diagnostic test method with a retrospective cross-sectional design. A total of 138 cases of thyroid nodules that received FNAB and anatomical pathology examinations were selected consecutively. The level of accuracy was determined from the number of sensitivity, specificity, positive predictive value and negative predictive value. Results: The results of this study showed a low sensitivity 11.53%, but high specificity 100%, positive predictive value 100%, and negative predictive value 82.96% of FNAB. The accuracy of FNAB as diagnostic tools of thyroid cancer was 83,3% compared with anatomical pathology results as gold standard. Conclusion: FNAB is less accurate to diagnose thyroid cancer, but FNAB examination is accurate in differentiate benign and cancer lesion in thyroid nodule.